Sacrospinous ligament fixation surgical outcoms after hysterectomy for apical support in a local population at a tertiary hospital - a retrospective descriptive study - Mokete, Gaone Gosego (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMed) -- Stellenbosch University, 2024.